Contracting colonialism from thesis to book to ebook - Totanes, Vernon R. (2013)
It is rare for scholarly books on Philippine history by Filipinos to remain in print twenty-five years after they were initially published. This research note examines the publishing history of Vicente Rafael’s Contracting Colonialism—from its origins as a doctoral thesis to its simultaneous publication by a US and a Philippine university press to its current availability as an ebook via two different platforms–to explore possible reasons behind its longevity and influence.
Keywords: Contracting Colonialism (Book); Electronic books; Filipino authors; Rafael, Vicente L